21 Monosomy in a retarded female infant. Issue 4 (December 1974) - Halloran, Katherine H.; Breg, W. Roy; Mahoney, Maurice J.
Abstract : A 20-month-old female infant with complete monosomy 21 is described. She has marked mental and physical retardation, antimongoloid slant, low set ears, micrognathia, syndactyly of the toes, and cardiac abnormalities. Karyotypes of fibroblasts and lymphocytes, examined with Giemsa banding, quinacrine banding, and reversed banding techniques revealed no evidence of translocation.